2020
DOI: 10.3390/biomedicines8050112
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells: A Trump Card for the Treatment of Diabetes?

Abstract: The advent of the new revolutionary approach based on regenerative medicine is progressively reshaping the therapeutic scenario of many different diseases, such as cardiovascular diseases and immune diseases, with encouraging results. During the last 10 years, many studies have also proposed the use of mesenchymal stem cells (MSCs), adult stem cells with several interesting properties already used in different experimental models, for the treatment of diabetes, however, reporting conflicting outcomes. These re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The capability of MSCs for immunomodulation has made them a useful treatment approach for inflammatory disorders such as multiple sclerosis [ 65 ], Crohn’s disease [ 66 ], GVHD [ 67 ], systemic lupus erythematosus [ 67 ], and type I diabetes [ 68 ]. Immunomodulation is dependent on crosstalk between MSCs and the immune microenvironment of the target tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The capability of MSCs for immunomodulation has made them a useful treatment approach for inflammatory disorders such as multiple sclerosis [ 65 ], Crohn’s disease [ 66 ], GVHD [ 67 ], systemic lupus erythematosus [ 67 ], and type I diabetes [ 68 ]. Immunomodulation is dependent on crosstalk between MSCs and the immune microenvironment of the target tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Across the last decade, it has been shown that the treatment with MSCs was able to induce islet regeneration, increase islet function, and inhibit immune system reactions in various animal models of T1D [ 131 ]. Kasahara et al found that AdMSCs-CM administered through a preservation solution was able to restore rat islets to the condition they were in before transport, culture, and transplantation [ 132 ].…”
Section: Mesenchymal Stem/stromal Cell (Msc)-based Therapy As a New S...mentioning
confidence: 99%